Method for producing zeolite

By integrating potassium in the alkali metal source and controlling the mixing process, the method addresses non-uniformity issues in large-scale zeolite production, achieving high-purity and crystalline zeolite efficiently.

JP2025010071APending Publication Date: 2025-01-20MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024106361
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-07-01
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing methods for producing zeolite on a large scale face challenges in achieving uniform mixing of raw materials, leading to non-uniform aqueous reactant precursors, which affects crystallinity and purity, resulting in low-quality zeolite production due to contamination by by-products and prolonged mixing times.

Method used

Incorporating a specific amount of potassium in the alkali metal element source during the preparation of the aqueous reactant precursor, followed by controlled mixing and aging in a stirred tank reactor, ensures uniformity and high crystallinity of zeolite production.

Benefits of technology

This method enables the production of highly pure and crystalline zeolite in large quantities by optimizing the mixing and aging processes, reducing impurities and shortening the production time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010071000015
    Figure 2025010071000015
  • Figure 2025010071000016
    Figure 2025010071000016
  • Figure 2025010071000017
    Figure 2025010071000017
Patent Text Reader

Abstract

To provide a production method for obtaining zeolite having high purity, and high crystallinity in large quantity by preparing a uniform raw material aqueous reaction product precursor for a short time, aging, and subjecting to hydrothermal synthesis.SOLUTION: A method for producing zeolite includes: a mixing process of mixing a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reaction product precursor; an aging process of aging the aqueous reaction product precursor; a raw material gel mixture-preparing process of adding at least another synthetic raw material containing a seed crystal to obtain a raw material gel mixture; and a hydrothermal synthesis process of subjecting the raw material gel mixture to hydrothermal synthesis, where an organic structure-stipulating agent is added in at least any step during the mixing process, the aging process or the raw material gel mixture-preparing process, between these processes, or before the hydrothermal synthesis process after the raw material gel mixture-preparing process, the mixing process is performed by a scale of 800 g charge amount or more in a stirred vessel-type reactor, an alkali metal constituting the alkali metal element source includes potassium, and the mole ratio of potassium in the alkali metals is 20% or more and 40% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a process for the preparation of zeolites, and more particularly to the preparation, aging and preparation of aqueous reactant precursors to zeolites using large scale stirred tanks. [Background technology]

[0002] Zeolites have properties such as a molecular sieve effect, ion exchange ability, catalytic ability, and adsorption ability due to the pores derived from their framework structure, and are currently widely used as adsorbents, ion exchange agents, industrial catalysts, and environmental catalysts.

[0003] In mass-scale production of zeolite, raw materials are generally added successively to a stirred tank reactor, an aqueous reactant precursor is prepared, aged, and then hydrothermal synthesis is performed. On the other hand, it is known that it is difficult to realize uniform mixing of raw materials depending on the composition of the aqueous reactant precursor. If aging and hydrothermal synthesis are performed in the state of the non-uniform aqueous reactant precursor, the crystal growth rate is affected, and as a result, the desired high-purity and high-crystalline zeolite cannot be obtained. For example, in Patent Document 1, AEI zeolite, which is considered to be particularly difficult to mass-produce, is produced in 0.1 liter units. In Patent Documents 2 and 3, etc., production is performed at the 1 liter level to obtain several hundred grams of AEI zeolite. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-81809 A [Patent Document 2] JP 2017-206417 A [Patent Document 3] JP 2021-147260 A Summary of the Invention [Problem to be solved by the invention]

[0005] According to the techniques disclosed in the above-mentioned Patent Documents 1 to 3, it is possible to produce a maximum of several hundred grams of zeolite. However, when a larger amount of zeolite is produced, preferably using a stirring tank of 2 liters or more, and particularly preferably using a stirring tank of 20 liters or more, there is a problem that a large amount of good quality zeolite cannot be produced due to a decrease in properties that is thought to be caused by a decrease in crystallinity and contamination with by-products other than the desired zeolite. In addition, when preparing a large amount of aqueous reactant precursor of a normal zeolite, it is mainstream to use a stirred tank type reactor. However, it is known that it is difficult to achieve uniform mixing in a short time depending on the physical properties of the prepared aqueous reactant precursor. In response to this, for example, when preparing a raw material aqueous reactant precursor having high viscosity, the order of addition of the zeolite synthesis raw materials, that is, the Si element source, Al element source, alkali metal element source, organic structure directing agent added as necessary, and water, and further the addition rate of the raw materials are usually controlled. However, in order to achieve a relatively uniform mixed state of the aqueous reactant precursor, a long mixing time (several hours to several tens of hours) was required. Furthermore, although it is a preferable embodiment to prepare the aqueous reactant precursor, age it, and synthesize it hydrothermally in the same stirred tank type reactor, a stirring system suitable for the physical properties of the aqueous reactant precursor and the gelation of the raw materials during hydrothermal synthesis has not been established. As a result, the aqueous reactant precursor becomes non-uniform, and there is a problem that the target zeolite with high purity and high crystallinity cannot be obtained.

[0006] Therefore, the object of the present invention is to provide a manufacturing method for obtaining a large amount of a high-purity, highly crystalline zeolite by preparing a uniform aqueous reactant precursor in a short time and performing aging and hydrothermal synthesis, and also to provide a manufacturing method for obtaining a large amount of such a high-purity, highly crystalline zeolite in a stirred tank reactor. [Means for solving the problem]

[0007] As a result of intensive research into the above-mentioned problems, the inventors have found that by adding an appropriate amount of a potassium element source to an alkali metal element source when mass-producing an aqueous reactant precursor in a stirring tank, gelation of the aqueous reactant precursor can be controlled and unevenness in the stirring tank, and ultimately in the hydrothermal reactor, can be eliminated, thereby making it possible to produce a target zeolite having high purity and high crystallinity, thereby solving the above-mentioned problems, and have arrived at the present invention.

[0008] That is, the gist of the present invention is as follows. [1] A method for producing a zeolite, comprising: a mixing step of mixing a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reactant precursor; an aging step of aging the aqueous reactant precursor; a raw gel mixture preparation step of adding other synthesis raw materials including at least seed crystals to obtain a raw gel mixture; and a hydrothermal synthesis step of hydrothermally synthesizing the raw gel mixture, wherein an organic structure directing agent is added at least at any stage of the mixing step, the aging step, the raw gel mixture preparation step, or between these steps, or after the raw gel mixture preparation step and before the hydrothermal synthesis step; the mixing step is carried out in a stirred tank reactor having a capacity of 800 g or more; the alkali metal constituting the alkali metal element source contains potassium, and the molar ratio of potassium in the alkali metal before the mixing step is 20% or more and 40% or less. [2] The method for producing a zeolite according to the above [1], wherein the mixing step, the aging step, the raw gel mixture preparation step, and the hydrothermal synthesis step are carried out in a stirred tank reactor. [3] The framework density of the zeolite is 14T / 1000Å. 3 Over 19T / 1000Å 3 A method for producing the zeolite according to the above [1] or [2], which is as follows: [4] The method for producing a zeolite according to any one of the above [1] to [3], wherein the zeolite has at least one of an 8-membered oxygen ring, a 10-membered oxygen ring, and a 12-membered oxygen ring. [5] The method for producing a zeolite according to any one of the above [1] to [4], wherein the ratio of the Si element source to the Al element source in the raw gel mixture is 5 or more and 1,000 or less, expressed as a molar ratio of the oxide of the Si element source to the oxide of the Al element source (molar ratio of SiO2 / Al2O3). [6] The ratio of the Si element source to the alkali metal element source contained in the aqueous reactant precursor is M (2 / n) O (M is an alkali metal element, and n is 1) molar ratio (M (2 / n) The method for producing a zeolite according to any one of the above [1] to [5], wherein the zeolite has a molecular weight of 0.02 or more and a molecular weight of 0.5 or less. [7] The method for producing a zeolite according to any one of the above [1] to [6], wherein in the mixing step, the aqueous reactant precursor further contains an alkaline earth metal element source. [8] The ratio of the Si element source, alkali metal element source, and alkaline earth metal element source contained in the aqueous reactant precursor is M to oxide of the Si element source. (2 / n) The molar ratio (M (2 / n) The method for producing a zeolite according to the above item [7], wherein the zeolite has a molecular weight of 0.02 or more and a molecular weight of 0.5 or less. Effect of the Invention

[0009] According to the present invention, a manufacturing method can be provided for preparing a uniform aqueous reactant precursor in a short period of time, and then aging and hydrothermal synthesis can be performed to obtain a large amount of high-purity, highly crystalline zeolite. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram of a typical stirred tank reactor used in the present invention. [Diagram 2]These are XRD patterns of typical target AEI type zeolite, impurity MOR type zeolite, impurity GME type zeolite, impurity MER type zeolite, impurity ANA type zeolite, and impurity sanidine (mineral, AlSi3O8). [Diagram 3] 1 is an XRD chart of the zeolites produced in Reference Examples 1 to 3 of the present invention. [Figure 4] 1 is an XRD chart of zeolites produced in Examples 1 to 3 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described in detail, but the following description is an example of the embodiment of the present invention, and the present invention is not limited to these contents. In addition, the embodiments of the present invention can be appropriately combined. In this specification, "to" means a range including the numerical values ​​described before and after it.

[0012] [Zeolite manufacturing method] The method for producing a zeolite of the present invention includes a mixing step of mixing a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reactant precursor, an aging step of aging the aqueous reactant precursor, a raw gel mixture preparation step of adding other synthesis raw materials including at least seed crystals to obtain a raw gel mixture, and a hydrothermal synthesis step of hydrothermally synthesizing the raw gel mixture, The mixing step is carried out in a stirred tank reactor having a capacity of 800 g or more, The alkali metal that constitutes the alkali metal element raw material contains potassium, and the molar ratio of potassium in the alkali metal before the mixing step is 20% or more and 40% or less. Here, the organic structure-directing agent is added at least at any stage during the mixing step, the aging step, the raw material gel mixture preparation step, or between these steps, or before the hydrothermal synthesis step after the raw material gel mixture preparation step. That is, it may be added during each of the above steps, or added between the mixing step and the aging step, between the aging step and the raw material gel mixture preparation step, or before the hydrothermal synthesis step after the raw material gel mixture preparation step. Note that the addition of the organic structure-directing agent may be made at any one stage or may be added at a plurality of stages.

[0013] Hereinafter, the raw materials used in the production method of the present invention will be described in more detail. <Si element source> The Si element source is a compound having Si atoms (hereinafter, may be described as "Si compound"). In the hydrothermal synthesis step, an amorphous Si compound is preferred because it is easily dissolved and inexpensive so as to obtain a Si / Al ratio (molar ratio) suitable for the crystallization of zeolite. Examples of the amorphous Si compound include amorphous silica such as colloidal silica, amorphous silica, fumed silica, and sodium silicate; trimethylethoxysilane, tetraethyl orthosilicate, aluminosilicate gel, etc. These may be used alone or in combination of two or more in any ratio. Also, from the viewpoint of being easily mixed uniformly with other raw materials and easily dissolved in water, colloidal silica, trimethylethoxysilane, tetraethyl orthosilicate, and aluminosilicate gel are preferred. Among the above, colloidal silica is particularly preferred as the Si element source.

[0014] <Al element source> The Al element source is a compound containing Al atoms (hereinafter, may be described as "Al compound"). The Al compound is preferably a compound that is easily soluble in water. In addition, it is preferably a compound that is well mixed with the Si compound and is easily soluble so that the Si / Al ratio (molar ratio) is suitable for crystallization of zeolite in the aging process, the raw material gel mixture preparation process, and the hydrothermal synthesis process. From the above viewpoints, the Al compound is preferably amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, aluminum hydroxide having a bayerite structure, aluminum nitrate, aluminum sulfate, aluminum oxide, sodium aluminate, boehmite, pseudo-boehmite, aluminum alkoxide, etc. These may be used alone or in any ratio and combination of two or more. Among these, particularly preferred are amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, and aluminum hydroxide having a bayerite structure. As the Al compound, it is preferred to use an amorphous aluminum element raw material, and among the above, amorphous aluminum hydroxide is particularly preferred.

[0015] (Amount of Al element source added) The Al element source is preferably used so that the ratio of the Si element source to the Al element source in the raw gel mixture before hydrothermal synthesis is such that the molar ratio of the oxide of the Si element source to the oxide of the Al element source (SiO2 / Al2O3 molar ratio) is 5 to 1000. By setting the SiO2 / Al2O3 molar ratio in the above range, the target zeolite can be easily obtained. From the above viewpoints, the SiO2 / Al2O3 molar ratio is more preferably in the range of 7 or more and 500 or less, further preferably in the range of 8 or more and 100 or less, and particularly preferably in the range of 10 or more and 30 or less.

[0016] <Alkaline metal element source> The alkali metal element source is not particularly limited, and may be a compound containing an alkali metal atom, and preferably, an alkali metal ion is contained in the aqueous reactant precursor before hydrothermal synthesis. As the alkali metal element source, inorganic acid salts such as hydroxides, oxides, sulfates, nitrates, phosphates, chlorides, bromides, and organic acid salts such as acetates, oxalates, and citrates of the above-mentioned alkali metal atoms can be used. The alkali metal element source may be used alone or in any combination of two or more kinds in any ratio. As the alkali metal element, known alkali metal elements used in the synthesis of zeolites can be used. Specifically, at least one selected from lithium, sodium, potassium, rubidium, and cesium is preferable. By including these alkali metal elements, the crystallization of zeolites can be easily promoted, and the amount of expensive OSDA added can be reduced. Among the above alkali metal elements, sodium and potassium are particularly preferred, and it is preferable to contain at least a potassium element source. The alkali metal elements may be used alone or in combination of two or more.

[0017] (mixed amount of alkali metal elements) The ratio of the Si element source to the alkali metal element source contained in the aqueous reactant precursor before hydrothermal synthesis is M to oxide of Si element. (2 / n) O (M is an alkali metal element, and n is 1) molar ratio (M (2 / n) The molar ratio of the oxide of the alkali metal element to the oxide of the Si element (M O / SiO2) is preferably 0.01 or more and 0.5 or less. Within this range, the target zeolite is easily obtained. From the above viewpoints, the ratio of the oxide of the alkali metal element to the oxide of the Si element (M (2 / n) The molar ratio of the alkali metal element to the Al atom contained in the aqueous reactant precursor is preferably 0.8 to 1.2. In addition, when several kinds of alkali metal elements are mixed, a mixture of sodium element and potassium element is preferable. In the present invention, it is particularly preferable that the alkali metal element contains at least potassium element. Furthermore, the molar ratio of potassium element to alkali metal element contained in the alkali metal element source before the mixing step is preferably 20% or more and 40% or less, more preferably 20% or more and 30% or less.

[0018] <Source of alkaline earth metal elements> In the production method of the present invention, in addition to the alkali metal source, an alkaline earth metal source may be further mixed in. Examples of the alkaline earth metal element include beryllium, magnesium, calcium, strontium, barium, etc. As the alkaline earth metal element source, the above-mentioned alkaline earth metal elements can be used in the form of inorganic acid salts such as hydroxides, oxides, sulfates, nitrates, phosphates, chlorides, bromides, etc., and organic acid salts such as acetates, oxalates, citrates, etc. The alkaline earth metal element raw materials can be used alone or in any combination of two or more kinds in any ratio.

[0019] (Mixing amount of alkali metal element source and alkaline earth metal element source) The ratio of the Si element source to the alkali metal element source and the alkaline earth metal element source contained in the aqueous reactant precursor is M to oxide of the Si element source. (2 / n) Molar ratio of O (M (2 / n) The O / SiO2 molar ratio is preferably 0.02 to 0.5, where M represents an alkali metal element or an alkaline earth metal element, and n is 1 for an alkali metal and 2 for an alkaline earth metal. That is, the total amount of the alkali metal source and the alkaline earth metal source (hereinafter sometimes referred to as "alkali") is preferably 0.02 or more and 0.5 or less in terms of the molar ratio to the oxide of the Si element source. When the amount of alkali is within the above range, the target zeolite is easily obtained. From the above viewpoint, the amount of alkali is more preferably in the range of 0.05 to 0.4.

[0020] (Amount of water added) The aqueous reactant precursor according to the present invention contains water (H2O) as an essential component. The amount of water added is usually 5 or more, preferably 7 or more, in terms of molar ratio to the Si atoms contained in the raw material gel mixture before hydrothermal synthesis, from the viewpoint of mitigating unevenness in heat and raw materials in the reactor and creating an environment in which zeolite is easily crystallized. From the viewpoint of reducing the amount of waste liquid to be treated, improving the one-batch efficiency (amount of zeolite recovered in one reactor), and enabling low-cost production by shortening the synthesis time, the amount of water to be added is usually 50 or less, preferably 40 or less, more preferably 30 or less, further preferably 25 or less, and particularly preferably 20 or less, in terms of the molar ratio to the Si atoms contained in the raw materials before hydrothermal synthesis. Water may be added in portions from the mixing step for obtaining the aqueous reactant precursor to the raw material gel mixture preparation step, or may be added all at once in any step.

[0021] <Method of preparing aqueous reactant precursor> The aqueous reactant precursor of the target zeolite according to the present invention is prepared by mixing an alkali metal element source, a Si element source, an Al element source, and water. The production method of the present invention is a production method including a step of aging the aqueous reactant precursor thus obtained, preferably in a stirred tank reactor (see FIG. 1), and a step of hydrothermally synthesizing the raw gel mixture through a raw gel mixture preparation step of adding other synthesis raw materials including at least seed crystals as the remaining raw materials before hydrothermal synthesis, thereby obtaining a raw gel mixture, and producing the target zeolite. That is, it is preferable to carry out the mixing step, the aging step, the raw gel mixture preparation step, and the hydrothermal synthesis step in a stirred tank reactor. The molar ratio of potassium is 20% or more and 40% or less with respect to the total amount of alkali metals contained in the alkali metal element source before the mixing step. As for the organic structure directing agent, as described above, it may be added in any step, and may be added in portions or all at once.

[0022] When mixing the aqueous reactant precursor, the order of adding each raw material is not particularly limited. From the viewpoint of easy control of viscosity change during mixing, however, it is preferable to add water containing an alkali metal element source to the Si element source and the Al element source.

[0023] (Mixing process) The mixing conditions of the Si element source, Al element source, alkali metal element source, and water are not particularly limited, but from the viewpoint of easily preparing a uniform raw material precursor, the average peripheral speed of the stirring blade of the stirring system is desirably 2 m / s or more, more desirably 7 m / s or more, and particularly preferably 10 m / s or more. On the other hand, from the viewpoint of reducing the load on the drive unit in system design and suppressing liquid splashing, it is desirably 30 m / s or less, more desirably 27 m / s or less, and particularly desirably 25 m / s or less.

[0024] (mixing time) The mixing time is not particularly limited, but from the viewpoint of purity and uniformity, a long mixing time is preferable. On the other hand, from the viewpoint of production efficiency, a short mixing time is preferable. Therefore, the mixing time is preferably 30 seconds or more, and particularly preferably 60 seconds or more. On the other hand, it is preferably 7200 seconds or less, more preferably 1800 seconds or less, and particularly preferably 600 seconds or less.

[0025] The peripheral speed can be calculated by the following procedure. Circumferential speed (m / s) = π × diameter of impeller (m) × (rotation speed) × (1 / 60) The peripheral speed does not necessarily have to be constant, and may change continuously. In such a case, when a constant mixing time a is given under a certain peripheral speed A, and then mixing is performed for a constant mixing time b under a peripheral speed B, the peripheral speed calculated by the following formula is defined as the average peripheral speed. In other words, the average peripheral speed is the product of the peripheral speed and the mixing time at each peripheral speed divided by the total mixing time. Average peripheral speed (m / s) = (peripheral speed A × a + peripheral speed B × b + ··· + peripheral speed N × n) / total mixing time (a + b + ··· + n) In the present invention, since stirring may be continued in the subsequent maturation step to prevent settling and to achieve more uniform mixing, the time during which stirring is continued in a state containing a Si element source, an Al element source, an alkali metal element source, and water at the aforementioned preferred peripheral speed, for example, a peripheral speed of 2 m or more, within the aforementioned preferred mixing time range may be regarded as the mixing step.

[0026] The viscosity and yield stress of the aqueous reactant precursor under room temperature conditions are not particularly limited, but from the viewpoint of facilitating the preparation of a uniform raw material precursor, the average viscosity of the precursor gel is preferably 5 dPa·s or less, more preferably 1 dPa·s or less, and even more preferably 0.65 dPa·s or less. For the same reason, the yield stress is preferably 100 Pa or less, more preferably 75 Pa or less, and even more preferably 50 Pa or less. On the other hand, from the viewpoints of solid yield, waste liquid treatment, and crystallization time, the average viscosity of the raw material precursor is preferably 0.01 dPa·s or more, more preferably 0.1 dPa·s or more, and even more preferably 0.3 dPa·s or more, in consideration of the substrate concentration. For the same reasons, the yield stress is preferably 1 Pa or more, more preferably 10 Pa or more, and even more preferably 30 Pa or more. In this mixing step, if the total amount of the Si element source and the like to be mixed is 800 g or more, the effect of the present invention is significantly obtained, and it is more preferable that the total amount is 2 kg or more, more preferably 10 kg or more, and even more preferably 40 kg or more. There is no particular upper limit, but considering the efficiency of removal, it is preferably 1000 kg or less, more preferably 500 kg or less. Also, when the size of the stirring tank during mixing is 1 liter or more, more preferably 2 liters or more, a significant effect is obtained, so it is preferable to use such a container. There is no particular upper limit, but it is usually 1000 liters or less, preferably 500 liters or less, more preferably 200 liters or less.

[0027] <Aging process> In the production method of the present invention, the aqueous reactant precursor obtained as described above is subjected to aging. (Aging process conditions) The temperature during the aging step is not particularly specified, but in order to avoid the generation of a poorly soluble crystalline precursor, the aqueous reactant precursor is aged at a temperature of preferably 140° C. or less, more preferably 120° C. or less, and particularly preferably 100° C. or less. The temperature may be constant during the aging, or may be changed stepwise or continuously.

[0028] (Aging time) The maturation time is not particularly limited. From the viewpoint of production efficiency, a short time is preferable, but from the viewpoint of purity and uniformity, it is preferable to carry out the maturation for a long time. Specifically, the maturation time is preferably 15 minutes or more, more preferably 30 minutes or more, and particularly preferably 60 minutes or more. On the other hand, it is preferably 36 hours or less, more preferably 24 hours or less, and particularly preferably 12 hours or less. The maturation is preferably carried out without applying external pressure because the apparatus required is simple. The maturation is preferably carried out with stirring since the raw materials are easily homogenized. The stirring method is not particularly limited.

[0029] <Raw material gel mixture preparation process> In the raw gel mixture preparation step, other synthesis raw materials including at least the seed crystals are added to obtain a raw gel mixture before hydrothermal synthesis. These are mixed in relatively small amounts and the hydrothermal synthesis step is performed immediately after, so that it is easy to mix them uniformly.

[0030] <Organic structure directing agent> In the present invention, it is preferable that an organic structure directing agent is contained in the raw material gel mixture before hydrothermal synthesis, and the content thereof is preferably 0.01 or more and 1 or less in molar ratio to Si atoms. In addition, since the organic structure directing agent is expensive among the synthesis raw materials, it is preferable to reduce the amount used. On the other hand, from the viewpoint of obtaining a high purity target zeolite, it is preferable to contain a certain amount or more of the organic structure directing agent. From the above viewpoint, that is, from the viewpoint of being able to obtain a high purity target zeolite while being inexpensive, the content of the organic structure directing agent is more preferably 0.02 or more in molar ratio to Si atoms, even more preferably 0.05 or more, and more preferably 0.5 or less, even more preferably 0.3 or less, and particularly preferably 0.15 or less. In addition, when preparing the mixed raw material for obtaining the aqueous reactant precursor, the organic structure directing agent may not be added or may be added in portions. The timing of adding the organic structure directing agent is preferably such that a part of it is added during the raw material gel mixture preparation process, but is not particularly limited. Therefore, it is also possible to add it as another synthesis raw material during the raw material gel mixture preparation process.

[0031] <Seed crystal> In the manufacturing method of the present invention, seed crystals are mixed in the raw material gel mixture preparation step of zeolite. The type of seed crystal is preferably zeolite, and the zeolite added as seed crystals in this manufacturing method has a framework density of 14T / 1000Å. 3 Over 19T / 1000Å 3 It is preferable that the zeolite has a density of 1000Å or less (hereinafter, this zeolite may be referred to as "zeolite added in the present invention"). Here, the framework density is a value described in ATLAS of zeolite framework types Sixth revised Edition, 2007, ELSEVIER by CH. Baerlocher et al., and is a value that represents the skeletal density. That is, the framework density is the value obtained by dividing the unit volume of the zeolite by 1000Å. 3 This refers to the number of T atoms (atoms other than oxygen atoms that make up the zeolite framework structure) present per unit area, and this value is determined by the structure of the zeolite. In addition, it is desirable that the seed crystals to be added have a common CBU (composite building unit) with the target zeolite. A CBU is formed by connecting TO4 units and is a structural unit of a zeolite. The seed crystals of zeolite to be added in the present invention may be one type of zeolite alone or two or more types in any ratio and combination. The seed crystals may be uncalcined products that have not been calcined after hydrothermal synthesis, calcined products that have been calcined after hydrothermal synthesis, or ion-exchanged products. Depending on the composition of the target zeolite (content, type, and water content of alkali metal atoms) and the synthesis environment (temperature, pH of the slurry), it is preferable to use uncalcined products under conditions where calcined products are easily dissolved.

[0032] The amount of seed crystals added is preferably 1% by mass or more relative to SiO2 when all of the Si atoms contained in the raw material before the hydrothermal synthesis are SiO2, and in order to promote crystallization, it is preferably 2% by mass or more, particularly preferably 3% by mass or more, and most preferably 5% by mass or more. The seed crystals are synthesized zeolite, and from the viewpoint of reducing production costs, it is preferably 20% by mass or less, particularly preferably 10% by mass or less.

[0033] <Hydrothermal synthesis process> In this production method, after aging, a raw material gel mixture preparation step is performed to obtain a predetermined raw material composition, followed by a hydrothermal synthesis step. The target zeolite is synthesized by hydrothermal synthesis. The hydrothermal synthesis is usually performed by placing the composition after the addition of zeolite in a pressure-resistant container and maintaining a predetermined temperature under self-generated pressure, while stirring, while rotating or rocking the container, or in a stationary state. The hydrothermal synthesis is usually performed at 140°C or higher. The hydrothermal synthesis is usually performed at 220°C or lower, preferably 200°C or lower, and more preferably 190°C or lower. The reaction time is not particularly limited, but is usually 2 hours or more, preferably 3 hours or more, more preferably 5 hours or more, and particularly preferably 12 hours or more, while it is usually 14 days or less, preferably 7 days or less, more preferably 5 days or less, and even more preferably 2 days or less. The reaction temperature may be constant during the reaction, or may be changed stepwise or continuously. The stirring speed may be constant during the reaction, or may be changed stepwise or continuously. By carrying out the hydrothermal synthesis under the above conditions, the yield of the target zeolite is improved, impurities are less likely to be produced, and the production costs can be reduced, which is preferable.

[0034] (Zeolite Recovery) After hydrothermal synthesis, the zeolite is separated from the composition after hydrothermal synthesis (hydrothermal synthesis reaction liquid). The obtained zeolite usually contains alkali metal atoms in the pores. Furthermore, when an organic structure-directing agent is used, the zeolite usually contains the organic structure-directing agent in the pores. Hereinafter, the substances contained in the pores of the zeolite after hydrothermal synthesis, such as the organic structure-directing agent or alkali metal, may be referred to as "structure-directing agent, etc.", and the zeolite containing this in the pores may be referred to as "SDA, etc.-containing zeolite." The method for separating the SDA-containing zeolite from the hydrothermal synthesis reaction liquid is not particularly limited, but typically includes filtration, decantation, direct drying, and the like.

[0035] The SDA-containing zeolite separated and recovered from the hydrothermal synthesis reaction liquid is washed with water, dried, and then calcined or otherwise treated to remove the structure-directing agent, etc., used during the production.

[0036] The method of removing the structure-directing agent from the SDA-containing zeolite can be a liquid phase treatment using an acidic solution or a chemical solution containing a structure-directing agent decomposing component, an ion exchange treatment using a resin, or a thermal decomposition treatment, or a combination of these treatments. The organic structure-directing agent contained in the zeolite can be removed by a method such as extraction with an organic solvent such as an ethanol aqueous solution. On the other hand, from the viewpoint of productivity, the organic structure-directing agent is preferably removed by firing. Usually, the zeolite is fired at a temperature of 300° C. or higher and 1000° C. or lower in air or an oxygen-containing inert gas, or in an inert gas atmosphere. The firing temperature is preferably 400° C. or higher, more preferably 450° C. or higher, and even more preferably 500° C. or higher, and is preferably 900° C. or lower, more preferably 800° C. or lower, and even more preferably 700° C. or lower. Nitrogen or the like can be used as the inert gas.

[0037] <Scope of the present invention> The production method of the present invention can be applied to various zeolites. Specific examples of particularly preferred zeolites include AEI type zeolite, CHA type zeolite, and CON type zeolite. In addition, the zeolite obtained by the present invention has a framework density of 14T / 1000Å. 3 Over 19T / 1000Å 3 It is preferable that: In particular, the zeolite preferably has at least one of an 8-membered oxygen ring, a 10-membered oxygen ring, and a 12-membered oxygen ring. The production method of the present invention is preferably applied to zeolites that are difficult to produce among the above-mentioned zeolites, and is particularly preferably applied to zeolites that are difficult to mass-produce. Among the above-mentioned zeolites, AEI zeolites are particularly susceptible to the influence of viscosity in both small-scale and large-scale production. Therefore, the production method of the present invention is particularly effective in producing AEI zeolites. Hereinafter, an explanation will be given taking AEI type zeolite, which is considered difficult to produce, as an example, but the production method of the present invention is not limited to these zeolites.

[0038] (AEI type zeolite) The zeolite produced by the production method of the present invention is AEI zeolite. In the present specification, AEI zeolite is taken as an example in the examples described later. Hereinafter, AEI zeolite will be described. The AEI zeolite exemplified in the examples is a code for the zeolite framework structure defined by the International Zeolite Association (IZA), which indicates an AEI structure. The structure is characterized by X-ray diffraction data. However, when actually measuring a produced zeolite, the intensity ratio and peak position of each peak may vary slightly due to the influence of the crystal face growth direction of the zeolite, the ratio of constituent elements, adsorbed substances, the presence of defects, etc., so the values ​​obtained are not exactly the same as the parameters of the AEI structure specified by the IZA, and a margin of about 10% is allowed. Major peaks observed in X-ray diffraction of AEI zeolite include, for example, the 110 plane peak at 2θ=9.5°±0.2°, the 022 plane peak at 16.9°±0.2°, and the 310 plane peak at 20.6°±0.2° when CuKα radiation is used as the radiation source.

[0039] This production method makes it possible to produce high-purity AEI zeolite on a large scale while reducing the amount of expensive organic structure-directing agents used.

[0040] As the purity of the target AEI zeolite increases, the performance such as catalytic activity when used as a catalyst improves. Therefore, the purity of the target AEI zeolite is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more. The higher the purity of the target zeolite, the better, and the upper limit is 100%.

[0041] The purity of AEI zeolite can be calculated by the following procedure. First, the by-product content in the zeolite is calculated. The by-product content can be calculated from the following formula (1) using an XRD pattern obtained by XRD measurement using CuKα radiation as a radiation source. By-product content (%) = I (peak intensity of by-product) / I (peak intensity of AEI zeolite + by-product) × 100 (1)

[0042] In the above formula (1), I(AEI) is the intensity of the main peak of AEI. The main peak is the most intense peak among the XRD peaks that characterize each zeolite, and in the case of AEI zeolite, it is typically the peak at 2θ=9.5°±0.2°. I(by-product) is the intensity of the main peak of the by-product. I(by-product) is the intensity of the XRD peak that characterizes the structure of the by-product. For example, when the by-product zeolite is a MOR type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=6.5±0.1°. When the by-product zeolite is a GME type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=7.5±0.1°. When the by-product zeolite is a MER type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=12.5±0.1°. When the by-product zeolite is an ANA type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=15.9±0.1°. When the by-product is sanidine, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=21.7±0.1°. When there are two or more types of by-products, I (by-products) is calculated by adding up the peak intensities.

[0043] From the by-product content (%) calculated as above, the purity of the AEI zeolite can be calculated from the following formula (2). Purity of AEI zeolite (%) = 100 - by-product content (%) (2)

[0044] (Applications of AEI zeolite) The use of the zeolite prepared in the present invention is not particularly limited, but it is preferably used as a catalyst, an adsorbent, a separation material, etc. Among them, it is preferable to use it as a catalyst or an adsorbent. The AEI zeolite of the embodiment is particularly preferably used as a catalyst for purifying exhaust gases of automobiles, etc. In addition, the AEI zeolite is also preferably used as an adsorbent for purifying exhaust gases of automobiles, etc. EXAMPLES

[0045] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples in any way as long as the gist of the present invention is not exceeded.

[0046] [Analysis and Evaluation] The zeolites obtained in the following Examples and Comparative Examples were analyzed by the following methods. <Powder XRD Measurement> (Sample preparation) 100 mg of a zeolite sample that had been manually crushed using an agate mortar was set in a sample holder of the same shape so that the sample amount was constant. (Apparatus specifications and measurement conditions) The specifications of the powder XRD measuring device and the measuring conditions are as follows.

[0047] [Table 1]

[0048] (Purity of AEI type zeolite) In the XRD pattern obtained by the XRD measurement, the purity of the AEI zeolite was calculated from the intensity of the main peak of the AEI zeolite and the intensity of the main peak of each by-product according to the above-mentioned formulas (1) and (2). Since there is a measurement background, when the peak intensity is 40 or less, it is defined as the background and is indicated by "-".

[0049] <Yield stress and average viscosity> (Viscosity measuring device) Rheometer MCR302 (manufactured by Anton Paar) Measuring device: Coaxial double cylindrical vessel (Sample preparation) The synthetic gel (pre-reaction mixture) was prepared in an amount of about 50 g and placed in the coaxial double cylinder of the rheometer. The yield stress and average viscosity of the synthetic gel were measured.

[0050] <Instrument specifications and measurement conditions> At room temperature, shear stress sweep test (1-100 Pa) and shear rate sweep test (1-100 s -1 ) and the average value of yield stress [Pa] and average viscosity (@100s -1 The viscosity of the gel was evaluated using two indices: viscosity at room temperature (°C) and viscosity at room temperature (Pa s). The measurement procedure is as follows. The first yield stress measurement in the stress sweep (1 - 100 Pa) mode was carried out. After 5 minutes, the second yield stress measurement was carried out. After another 5 minutes, the third yield stress measurement was carried out. The yield stress was calculated by averaging the three measured values. Subsequently, it was switched to the shear rate sweep test. After 5 minutes, the measurement was carried out, and the shear rate was 100 s -1 The viscosity at was taken as the average viscosity (@100 s -1 ).

[0051] <Method for preparing the measurement sample> The measurement sample has the same molar composition as the synthetic gels of Example 1, Comparative Example 2, and Reference Example 3. Each sample was prepared, 50 g was taken, and set in the coaxial double cylinder of the rheometer. The detailed preparation procedure is as follows.

[0052] <<When the ratio of K is 0>> 2.79 g of NaOH (manufactured by Wako Pure Chemical Industries, Ltd.) was added to 39.68 g of water, stirred and dissolved to prepare a transparent solution. 2.6 g of amorphous Al(OH)3 (Al2O3, 53.5 mass%, manufactured by Kyowa Chemical Industry Co., Ltd.) was added. After stirring for about 5 minutes, 26.77 g of colloidal silica SiO2 (SiO2, 40.2 mass%, manufactured by Nissan Chemical Industries, Ltd.) was added and stirred for about 5 minutes. The prepared synthetic gel was introduced into a 200 ml mill bottle and mixed at room temperature for 1 minute to prepare an aqueous reactant precursor which is a synthetic gel equivalent to Comparative Example 2.

[0053] <<When the ratio of K is 0.25>> 2.05 g of NaOH (manufactured by Wako Pure Chemical Industries, Ltd.) and 1.19 g of KOH (manufactured by Wako Pure Chemical Industries, Ltd.) were added to 39.52 g of water, stirred and dissolved to prepare a transparent solution. 2.6 g of amorphous Al(OH)3 (Al2O3, 53.5 mass%, manufactured by Kyowa Chemical Industry Co., Ltd.) was added. After stirring for about 5 minutes, 26.77 g of colloidal silica SiO2 (SiO2, 40.2 mass%, manufactured by Nissan Chemical Industries, Ltd.) was added and stirred for about 5 minutes. The prepared synthetic gel was introduced into a 200 ml mill bottle and mixed at room temperature for 1 minute to prepare an aqueous reactant precursor which is a synthetic gel equivalent to Example 1.

[0054] <<When the ratio of K is 0.5>> 1.31 g of NaOH (manufactured by Wako Pure Chemical Industries, Ltd.) and 2.38 g of KOH (manufactured by Wako Pure Chemical Industries, Ltd.) were added to 39.67 g of water, stirred and dissolved to prepare a clear solution. 2.6 g of amorphous Al(OH)3 (Al2O3, 53.5 mass%, manufactured by Kyowa Chemical Industry Co., Ltd.) was added, and after stirring for about 5 minutes, 26.77 g of colloidal silica SiO2 (SiO2, 40.2 mass%, manufactured by Nissan Chemical Industries, Ltd.) was added, and stirred for about 5 minutes. The prepared synthetic gel was introduced into a 200 ml mill bottle, mixed at room temperature for 1 minute, and an aqueous reaction precursor equivalent to Reference Example 3 was prepared.

[0055] [Reference Example 1] 0.34 g of NaOH (manufactured by Wako Pure Chemical Industries, Ltd., 97 mass%) and 0.20 g of KOH (manufactured by Wako Pure Chemical Industries, Ltd., 85 mass%) were added to 5.7 g of water, stirred for 300 seconds (s) to prepare an alkaline aqueous solution. Then, 0.43 g of amorphous Al(OH)3 (Al2O3, 53.5 mass%, manufactured by Kyowa Chemical Industry Co., Ltd.) was added, and stirred for another 300 seconds (s). 4.46 g of colloidal silica SiO2 (SiO2, 40.2 mass%, manufactured by Nissan Chemical Industries, Ltd.) was added to prepare a white suspension. It was mixed at room temperature for 2 h under low circumferential speed conditions (average circumferential speed is 3 m / s) on a 100 cc scale. The prepared aqueous reaction precursor was placed in a 100 cc autoclave and aged at 80 °C under static conditions for 2 h. To the aged mixture, 1.4 g of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seikem) as an organic structure directing agent (OSDA) was added, stirred for 300 seconds (s), and then 0.09 g of an uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000 Å 3 :Si / Al (SAR) = 23) was mixed and stirred at room temperature for 30 min to obtain a raw material gel mixture. The gel before hydrothermal synthesis after the preparation process of the raw material gel mixture is called the raw material gel mixture. The molar composition ratios of the raw material gel mixture other than the seed crystal are shown below. SiO2: 0.077Al2O3: 0.3NaOH: 0.1KOH: 17.5H2O: 0.1OSDA

[0056] This raw gel mixture was placed in a 100 cc autoclave and hydrothermal synthesis was carried out for 24 hours while stirring the container (15 rpm) at a temperature of 180 ° C. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100 ° C. for 12 hours. When the XRD of the obtained powder 1 was measured, an XRD pattern with peaks and relative intensities at the positions shown in Table 2 in lattice spacing was observed, and the synthesis of AEI type zeolite was confirmed. The XRD pattern of this powder 1 is shown in Figure 3. In Figure 3, the vertical axis is intensity (cps) and the horizontal axis is diffraction angle 2θ (°). The proportion of AEI type zeolite in powder 1 was 100%.

[0057] [Table 2]

[0058] [Example 1] 38 g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, manufactured by Kyoward Chemical) was added to 300 g of water, and 394 g of colloidal silica SiO2 (SiO2, 40.2% by mass, manufactured by Nissan Chemical) was added to prepare a slurry A-1 solution. 30 g of NaOH (manufactured by Wako Pure Chemical Industries, Ltd.), 18 g of KOH (manufactured by Wako Pure Chemical Industries, Ltd.), and 177 g of water were mixed and stirred to dissolve, preparing a transparent solution B-1. The transparent solution B-1 was added to the slurry A-1, and mixed at room temperature for 3 min using a 2 L scale mixer to prepare an aqueous reactant precursor. 0.95 kg of the prepared aqueous reactant precursor was placed in a 2 L-scale stirred tank reactor, and then aged at 80°C for 4 hours while stirring at 240 rpm using a Fullzone impeller (3 baffles). To the aged mixture, 119 g of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA). Finally, 11.9 g of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals. 3The raw gel mixture was obtained by mixing SiO2 / Al2O3 (SAR = 23) with 30 g of water and stirring for 30 min at room temperature. The molar composition ratio of the raw material gel mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0059] This raw gel mixture was stirred (360 rpm) at a temperature of 180 ° C. for 15 hours to carry out hydrothermal synthesis. At this time, a full zone blade was used in the stirring tank type reactor, and three baffles were used. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100 ° C. for 12 hours. When the XRD of the obtained powder 2 was measured, the XRD pattern shown in Figure 4 was shown, and the XRD pattern had peaks and relative intensities at the positions shown in Table 3 in the lattice spacing representation, and it was confirmed that AEI type zeolite was synthesized. The proportion of AEI type zeolite in powder 2 was 100%.

[0060] [Table 3]

[0061] [Example 2] 40.4 g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, manufactured by Kyoward Chemical) was added to 300 g of water, and 416.4 g of colloidal silica SiO2 (SiO2, 40.2% by mass, manufactured by Nissan Chemical) was added to prepare a slurry A-2 solution. 31.8 g of NaOH (manufactured by Wako Pure Chemical Industries, 97% by mass), 18.5 g of KOH (manufactured by Wako Pure Chemical Industries, 85% by mass), and 140 g of water were mixed and stirred to dissolve, preparing a transparent solution B-2. The transparent solution B-2 was added to the slurry A-2 and mixed at room temperature for 1.5 min using a 2 L scale mixer. The same procedure was repeated a total of 44 times to prepare the aqueous reactant precursor. 39.78 kg of the prepared aqueous reactant precursor was placed in a 100 L scale stirred tank reactor, and then aged at 80°C for 6 hours while stirring at 120 rpm using a Max Blend blade (two baffles). After aging, 5.3 kg of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA) to the mixture after aging, and then 1.5 kg of water was sprinkled on it for washing. Finally, 0.7 kg of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals. 3 The raw gel mixture was obtained by mixing SiO2 / Al2O3 (SAR = 23) with 2.5 kg of water and stirring for 30 min at room temperature. The molar composition ratio of the raw material gel mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0062] This raw gel mixture was stirred (80 rpm) at a temperature of 180 ° C. for 16 hours to carry out hydrothermal synthesis. At this time, a Max Blend blade was used in the stirring tank type reactor, and two baffles were used. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100 ° C. for 12 hours. When the XRD of the obtained powder 3 was measured, the XRD pattern shown in Figure 4 was obtained, and the lattice spacing was represented by peaks and relative intensities at the positions shown in Table 4, and it was confirmed that AEI type zeolite was synthesized. The proportion of AEI type zeolite in powder 3 was 93.4%.

[0063] [Table 4]

[0064] [Example 3] 3474.4g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, manufactured by Kyoward Chemical) was added to 25800g of water, and 35810.4g of colloidal silica SiO2 (SiO2, 40.2% by mass, manufactured by Nissan Chemical) was added to prepare a slurry A-3 solution. 2734.8g of NaOH (manufactured by Wako Pure Chemical Industries, Ltd.), 1589.3g of KOH (manufactured by Wako Pure Chemical Industries, Ltd.), and 12040g of water were mixed and stirred to dissolve, preparing a transparent solution B-3. The transparent solution B-3 was added to the slurry A-3, and mixed at room temperature for 12 min using a 150L scale high peripheral speed agitator (average peripheral speed of the agitating blade was 11 m / s). 78.0 kg of the prepared aqueous reactant precursor was placed in a 100 L scale stirred tank reactor, and then aged for 6 hours at 80°C while stirring at 120 rpm using a Max Blend impeller (two baffles). After aging, 10.4 kg of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added to the mixture after aging as an organic structure directing agent (OSDA), and then 2.3 kg of water was sprinkled on it for washing. Finally, 1.4 kg of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals. 3 The raw gel mixture was obtained by mixing SiO2 / Al2O3 (SAR = 23) with 5.6 kg of water and stirring for 30 min at room temperature. The molar composition ratio of the raw material gel mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0065] This raw gel mixture was stirred (90 rpm) at a temperature of 180 ° C. for 20 hours to carry out hydrothermal synthesis. At this time, a Max Blend blade was used in the stirring tank type reactor, and two baffles were used. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100 ° C. for 12 hours. When the XRD of the obtained powder 4 was measured, the XRD pattern shown in Figure 4 was obtained, and the lattice spacing was represented by peaks and relative intensities at the positions shown in Table 5, and it was confirmed that AEI type zeolite was synthesized. The proportion of AEI type zeolite in powder 4 was 100%.

[0066] [Table 5]

[0067] [Example 4] 3474.4 g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, manufactured by Kyoward Chemical) was added to 25800 g of water, and 35810.4 g of colloidal silica SiO2 (SiO2, 40.2% by mass, manufactured by Nissan Chemical) was added to prepare a slurry A-4 solution. 2734.8 g of NaOH (manufactured by Wako Pure Chemical Industries, Ltd.), 1589.3 g of KOH (manufactured by Wako Pure Chemical Industries, Ltd.), and 12040 g of water were mixed and stirred to dissolve, preparing a transparent solution B-4. The transparent solution B-4 was added to the slurry A-4, and mixed at room temperature for 12 min using a 150 L scale high peripheral speed stirrer (average peripheral speed of the stirring blade was 11 m / s). The same gel mixing process was repeated a total of 23 times. 1555.7 kg of the prepared aqueous reactant precursor was placed in a 2000 L scale stirred tank reactor, and then aged for 6 hours at 80°C while stirring at 30 rpm using a Supermix blade (two baffles) ("MR205" manufactured by Satake Multimix Co., Ltd.). After aging, 208.1 kg of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA) to the mixture after aging, and then 40 kg of water was sprinkled on it for washing. Finally, 27.6 kg of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals.3 The raw gel mixture was obtained by mixing SiO2 / Al2O3 (SAR = 23) in 50 kg of water and stirring for 30 min at room temperature. The molar composition ratio of the raw material gel mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0068] This raw gel mixture was stirred (45 rpm) at a temperature of 180°C and hydrothermal synthesis was carried out for 22 hours. At this time, a Supermix blade was used in the stirring tank type reactor, and two baffles were used. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100°C for 12 hours. When the XRD of the obtained powder 5 was measured, it was confirmed that the lattice spacing had peaks and relative intensities at the positions shown in Table 6, and that AEI type zeolite was synthesized. The proportion of AEI type zeolite in powder 5 was 100%.

[0069] [Table 6]

[0070] [Reference example 2] 0.46g of NaOH (Wako Pure Chemical Industries, Ltd.) was added to 5.7g of water and stirred for 300s to prepare an alkaline aqueous solution, after which 0.43g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, Kyoward Chemical Industries, Ltd.) was added and stirred for another 300s. 4.5g of colloidal silica SiO2 (SiO2, 40.2% by mass, Nissan Chemical Industries, Ltd.) was added to prepare a white suspension. The mixture was mixed for 30min at room temperature under low peripheral speed conditions (average peripheral speed was 3m / s) in a 100cc scale. The prepared aqueous reactant precursor was placed in a 100 cc autoclave and aged for 2 hours under stationary conditions at 80°C. To the aged mixture, 1.36 g of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA), and the mixture was stirred for 300 seconds. After that, 0.09 g of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as a seed crystal. 3 The raw gel mixture was obtained by mixing SiO2 / Al2O3 (SAR = 23) and stirring at room temperature for 30 min. The molar composition ratio of the raw material gel mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.4NaOH:17.5H2O:0.1OSDA

[0071] This raw gel mixture was placed in a 100 cc autoclave, and hydrothermal synthesis was carried out for 24 hours while stirring the container (15 rpm) at a temperature of 180 ° C. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100 ° C. for 12 hours. When the XRD of the obtained powder 6 was measured, an XRD pattern having peaks and relative intensities at the positions shown in Table 7 in lattice spacing was observed, and the synthesis of AEI type zeolite was confirmed. The XRD pattern of this powder 6 is shown in Figure 3. In Figure 3, the vertical axis is intensity (cps) and the horizontal axis is diffraction angle 2θ (°). The proportion of AEI type zeolite in powder 6 was 100%.

[0072] [Table 7]

[0073] [Comparative Example 1] 440g of water and 43.3g of amorphous Al(OH)3 (Al2O3 53.5% by mass, Kyoward Chemical Co., Ltd.) were added, 309g of colloidal silica SiO2 (SiO2, 40.2% by mass, Nissan Chemical Co., Ltd.) were added, and 135.7g of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide 35.2% aqueous solution (Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA) to prepare a slurry A-5 solution. 46.4g of NaOH (Wako Pure Chemical Industries, Ltd., 97% by mass) was dissolved in 134g of water to prepare a transparent solution B-5. The transparent solution B-5 was slowly dripped into the slurry A-5 (0.5cc / min), and an aqueous alkaline solution was added to prepare an aqueous reactant precursor. The remaining colloidal silica SiO2 (SiO2, 40.2 mass%, Nissan Chemical) (137 g) was added, and the mixture was aged for 1 hour while stirring (240 rpm) at room temperature. After aging, 9.0 g of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000 Å) was added as seed crystals to the mixture. 3 The raw gel mixture was obtained by mixing SiO2 / Al2O3 (SAR = 23) with 30 g of water and stirring for 60 min at room temperature. The molar composition ratio of the raw material gel mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.4NaOH:17.5H2O:0.1OSDA

[0074] This raw gel mixture was stirred (150 rpm) at a temperature of 180°C and hydrothermal synthesis was carried out for 24 hours. At this time, a paddle blade was used for the stirring tank type reactor. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100°C for 12 hours. When the XRD of the obtained powder 7 was measured, an XRD pattern with peaks and relative intensities at the positions shown in Table 8 in lattice spacing was shown, and it was confirmed that AEI type zeolite was synthesized. The XRD pattern of the powder 7 is shown in Fig. 4. In Fig. 4, the vertical axis represents intensity (cps) and the horizontal axis represents the diffraction angle 2θ (°). The proportion of AEI zeolite in the powder 7 was 50%.

[0075] [Table 8]

[0076] [Comparative Example 2] 292g of water, 34.7g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, Kyoward Chemical Co., Ltd.), and 356.9g of colloidal silica SiO2 (SiO2, 40.2% by mass, Nissan Chemical Co., Ltd.) were added to prepare slurry A-6. 37.2g of NaOH (Wako Pure Chemical Industries, Ltd.) and 107g of water were mixed and stirred to dissolve, preparing transparent solution B-6. Transparent solution B-6 was added to slurry A-6 and mixed at room temperature for 2 min using a 2L scale mixer. The same procedure was repeated a total of 50 times to prepare an aqueous reactant precursor. 41.37 kg of the prepared aqueous reactant precursor was placed in a 100 L scale stirred tank reactor, and then aged at 80°C for 6 hours while stirring at 60 rpm using a Max Blend blade (two baffles). After aging, 5.4 kg of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA) to the mixture after aging, and then 1.5 kg of water was sprayed on it for washing. Finally, 1.08 kg of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals. 3 The raw gel mixture was obtained by mixing 1.5 kg of water and stirring for 30 min at room temperature. The molar composition ratio of the raw material gel mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.4NaOH:17.5H2O:0.1OSDA

[0077] This raw gel mixture was stirred (60 rpm) at a temperature of 185°C and hydrothermal synthesis was carried out for 24 hours. At this time, a Max Blend blade was used in the stirring tank type reactor, and two baffles were used. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100°C for 12 hours. When the XRD of the obtained powder 8 was measured, an XRD pattern with peaks and relative intensities at the positions shown in Table 9 in lattice spacing was shown, and it was confirmed that AEI type zeolite was synthesized. The XRD pattern of this powder 8 is shown in Figure 4. In Figure 4, the vertical axis is intensity (cps) and the horizontal axis is diffraction angle 2θ (°). The proportion of AEI zeolite in powder 8 was 39%.

[0078] [Table 9]

[0079] [Reference example 3] 0.22g of NaOH (Wako Pure Chemical Industries, Ltd.) and 0.4g of KOH (Wako Pure Chemical Industries, Ltd.) pellets were added to 5.7g of water and stirred for 300s to prepare an alkaline aqueous solution, after which 0.43g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, Kyoward Chemical Industries, Ltd.) was added and stirred for another 300s. 4.5g of colloidal silica SiO2 (SiO2, 40.2% by mass, Nissan Chemical Industries, Ltd.) was added to prepare a white suspension. Mixing was performed for 2h at room temperature under low peripheral speed conditions (average peripheral speed was 3m / s) in a 100cc scale. The prepared aqueous reactant precursor was placed in a 100cc autoclave and aged for 2h under stationary conditions at 80°C. To the mixture after aging, 1.36 g of 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA), and the mixture was stirred for 300 s. After that, 0.09 g of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000 Å) was added as a seed crystal. 3 The raw gel mixture was obtained by mixing SiO2 / Al2O3 (SAR = 23) and stirring at room temperature for 30 min. The molar composition ratio of the raw material gel mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.2NaOH:0.2KOH:17.5H2O:0.1OSDA

[0080] This raw gel mixture was placed in a 100 cc autoclave, and hydrothermal synthesis was carried out for 24 hours while stirring (15 rpm) the entire container at a temperature of 180°C. After the hydrothermal synthesis reaction, the reaction solution was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100°C for 12 hours. When the XRD of the obtained powder 9 was measured, an XRD pattern with peaks and relative intensities at the positions shown in Table 10 in lattice spacing was observed, and it was confirmed that AEI type zeolite was synthesized. The XRD pattern of powder 9 is shown in Fig. 3. In Fig. 3, the vertical axis represents intensity (cps) and the horizontal axis represents the diffraction angle 2θ (°). The proportion of AEI zeolite in powder 9 was 77%.

[0081] [Table 10]

[0082] For Reference Examples 1 to 3, Examples 1 to 4, and Comparative Examples 1 and 2, the conditions for preparing the raw material gel mixture of the aqueous reactant precursor and the conditions for hydrothermal synthesis are summarized in Table 11 (Tables 11-1 and 11-2). The evaluation results for the Reference Example, each Example, and Comparative Example are shown in Tables 12 and 13. In Table 12, the K ratio in the alkali metals of 0 is the measurement result for Comparative Example 2, the K ratio of 0.25 is the measurement result for Example 1, and the K ratio of 0.5 is the measurement result for Reference Example 3.

[0083] [Table 11]

[0084] [Table 12]

[0085] [Table 13]

[0086] [Table 14]

[0087] From the above examples, it was confirmed that the viscosity of the aqueous reactant precursor and raw gel mixture can be controlled by adjusting the ratio (0-0.5) of potassium (K) in the alkali metal. It was also confirmed that a high-purity target zeolite (AEI type in the examples) can be obtained in a stirred tank reactor by using an aqueous reactant precursor with an average viscosity of 0.25-0.76 Pa s and a yield stress of 25 to 50 Pa under room temperature conditions, followed by aging, preparation of a raw gel mixture, and further hydrothermal synthesis. Here, in each Example (2L to 2000L), when the ratio of K is 0.25, a high-purity target zeolite can be synthesized at any scale, and when the ratio of K is 0, a high-purity target zeolite is obtained in Reference Example (small scale of 100cc), but a large amount of impurities is generated in Comparative Examples 2 and 3. In other words, when the molar ratio of potassium (K) in the alkali metal elements is 0, it can be inferred that the viscosity of the synthesis gel is unsuitable for a stirred tank type reactor. Also, when the ratio of potassium (K) is 0.5, in Reference Example 3 (small scale of 100cc), despite the decrease in viscosity, the purity of the target zeolite is low, so it can be inferred that the target zeolite deviates from the optimal synthesis composition range. [Industrial Applicability]

[0088] According to the production method of the present invention, a homogeneous raw aqueous reactant precursor and raw gel mixture can be prepared in a short time even on a large scale by a simple method of controlling the ratio of potassium in the alkali metal. The precursor is then aged, and the raw gel mixture obtained by adding seed crystals and SDA is then hydrothermally synthesized to obtain a large amount of high-purity and highly crystalline zeolite. Zeolites can be used as various materials, and are widely used, for example, as adsorbents, ion exchange agents, industrial catalysts, and environmental catalysts. The method of the present invention, which can efficiently produce such zeolites, is an industrially important technology and can contribute to industry.

Claims

1. A method for producing a zeolite, comprising: a mixing step of mixing a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reactant precursor; an aging step of aging the aqueous reactant precursor; a raw gel mixture preparation step of adding other synthesis raw materials including at least seed crystals to obtain a raw gel mixture; and a hydrothermal synthesis step of hydrothermally synthesizing the raw gel mixture, adding an organic structure directing agent at least at any stage of the mixing step, the aging step, the raw material gel mixture preparation step, or between these steps, or after the raw material gel mixture preparation step and before the hydrothermal synthesis step; The mixing step is carried out in a stirred tank reactor having a capacity of 800 g or more, The method for producing a zeolite, wherein the alkali metal constituting the alkali metal element source contains potassium, and the molar ratio of potassium in the alkali metal before the mixing step is 20% or more and 40% or less.

2. 2. The method for producing a zeolite according to claim 1, wherein the mixing step, the aging step, the raw gel mixture preparation step, and the hydrothermal synthesis step are carried out in a stirred tank reactor.

3. The framework density of the zeolite is 14T / 1000Å. 3 Over 19T / 1000Å 3 The method for producing the zeolite according to claim 1, wherein:

4. The method for producing a zeolite according to claim 1, wherein the zeolite has at least one of an 8-membered oxygen ring, a 10-membered oxygen ring, and a 12-membered oxygen ring.

5. The ratio of the Si element source to the Al element source in the raw gel mixture is a molar ratio of the oxide of the Si element source to the oxide of the Al element source (SiO 2 / Al 2 O 3 The method for producing a zeolite according to claim 1, wherein the molar ratio of the zeolite to the zeolite is 5 or more and 1,000 or less.

6. The ratio of the Si element source to the alkali metal element source contained in the aqueous reactant precursor is M (2 / n) O (M represents an alkali metal element, and n is 1) molar ratio (M (2 / n) O / SiO 2 The method for producing a zeolite according to claim 1, wherein the molar ratio of the zeolite to the zeolite is 0.01 or more and 0.5 or less.

7. 2. The method for producing a zeolite according to claim 1, wherein in the mixing step, the aqueous reactant precursor further comprises a source of an alkaline earth metal element.

8. The ratio of the Si element source, the alkali metal element source, and the alkaline earth metal element source contained in the aqueous reactant precursor is M (2 / n) O (M represents an alkali metal element and an alkaline earth metal element, n is 1 for an alkali metal and 2 for an alkaline earth metal) molar ratio (M (2 / n) O / SiO 2 The method for producing a zeolite according to claim 7, wherein the molar ratio of the zeolite to the zeolite is 0.02 or more and 0.5 or less.

Citation Information

Patent Citations

  • AEI zeolite and manufacturing method and application thereof

    JP2017081809A

  • Method for producing AEI type zeolite

    JP2017206417A

  • Production method of AEI zeolite, catalyst, and adsorbent

    JP2021147260A